Pataru Sere Sahatan Dalam Perspektif ‘Urf - Zulfan Efendi Hasibuan (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Batak tradition is a tradition that is rich with a diversity of ways of implementation, different regions have different customs, especially the Angkola Batak tradition. The Batang Angkola custom regulates marriage issues, the most prominent thing in the case of marriage in the Batak Angkola custom is the pre-wedding process, including the Pataru Sere Sahatan tradition which is one of a series of events in the Batak Angkola traditional wedding. If translated according to a series of Islamic marriage laws, this process is called the delivery of the dowry, but there is a series of different activities because it is influenced by the Batang Angkola custom, so it is necessary to examine it further, using an 'Urf perspective.